Influence of Dietary Energy and Lysine Concentration on Layer Hen Performance and Egg Quality During Peak Production - Gert Coertze; Rene Kwakkel; Laura Star; Christine Jansen van Rensburg (Poultry, 2025)
Limited published data areavailable on the current DLys requirements of Hy-Line Silver-Brown layers. The effects of energy (AMEn) and standardized ileal digestible lysine (DLys) concentration on the performance of Hy-Line Silver-Brown layers were studied from 20 to 35 weeks of age. The experimental design was randomized with twenty-four dietary treatments arranged as a 2 × 12 factorial with two AMEn concentrations (2750 and 2900 kcal/kg feed) and twelve levels of DLys (4.2, 4.5, 4.8, 5.1, 5.4, 5.7, 6.0, 6.6, 6.3, 6.9, 7.2, and 7.5 g/kg). Total egg weight (TEW), average egg weight, total egg number (TEN), laying rate, total feed intake, average daily feed intake (ADFI), mortality, hen body weight, hen body weight gain, eggshell thickness, eggshell breaking strength, yolk weight, albumen weight, and eggshell weight were recorded. An increase in energy content from 2750 to 2900 kcal AMEn/kg reduced ADFI (p < 0.001), egg mass output (p = 0.042), and feed conversion ratio (p = 0.018, g/g; p = 0.001, g/dozen) and increased the fat percentage in the liver (p = 0.028). An increased DLys intake from 529 to 882 mg/hen/day increased the TEN (p = 0.001), TEW (p < 0.001), and egg mass output (p < 0.001); improved the feed conversion ratio (p < 0.001); and reduced carcass (p = 0.001) and liver fat percentage (p = 0.05). Hy-Line Silver-Brown hens require no more than 780 mg (optimized egg production) and 880 mg (maximized egg weight) DLys/hen/day during pre-peak and peak production phases.